Ceux qui partent et celles qui restent - Catherine Brice (Diasporas: Circulations, Migrations, Histoire)
This article examines the role of women, whether wives, mothers, sisters or daughters, in the economic links between exiles and those who remain in their country of departure. Between the exiles and their family, a system of “remote” management of property – or sometimes confiscated or sequestered property that need to be recovered – is implemented. In this configuration, women are particularly active because they have to recover and administer the goods, in particular their dowries. Thus the women who remain gain greater autonomy, making their own decisions about patrimonies, and playing with their supposed political “incapacity” to become intermediaries with the authorities.